To Reveal or Not to Reveal? Observation of Social Outcomes Facilitates Reward Processing - Shen, Qiang; Zhu, Lian; Meng, Liang; Qiu, Wenwei; Ma, Qingguo; Ebstein, Richard P.; Jin, Jia (Frontiers in Neuroscience, 2021)
Motivation is a key topic that comprises of considerable theoretical and practical implications and its study is gaining increasing traction in recent years. Employing both behavioral and neural techniques, previous studies examined the extent to which intrinsic and extrinsic motivations collectively shape individual decision making. Investigations found that both processes play indispensable and interactive roles in choice behavior. However, despite its importance, little is known respecting the role of extrinsic social factors in contributing to individual variations in intrinsic motivation. Towards elucidating the role of extrinsic social factors in motivated decision making, the current study implements the stop watch task, combined with hyper-recording electrophysiological measurements. With the electrophysiological toolkit, our goal is to bring to light how extrinsic social signals impact intrinsic motivation and shape the reward processing over success and failure at the succeeding stage. Empirically, we show that, following social outcome presentation, there is an increased divergent feedback-related negativity (FRN), which reflects the failure/success discrepancy at the outcome stage of choice behavior. In summary, this study demonstrates the saliency of social information in intrinsic motivational processes that underpin success-failure outcomes.